SPATIAL DEVELOPMENT OF TERRITORIES: STATUS, TRENDS, INTEGRATED APPROACH TO ASSESSING THE DIFFERENTIATION OF REGIONS (TERRITORIES) - L. A. Tretyakova; A. S. Astakhin (Вестник университета)
The trends and problems of spatial development of regions of Russia in the context of integration of the domestic economy in the transition period from the planned socialist to the capitalist system of economic relations on the example of Vladimir region have been analysed. A methodology for assessing regional differentiation has been proposed. Aspect novelty of the estimation methodology consists in a unified comparative analysis of empirical integrated indicators obtained by calculating partial values of criterion-factors by means of converging integer series using methods of limit equations in combination with the method of Lyapunov's functions in comparison with threshold values of the corresponding integrated indicators. At the same time integrated indicators meet the requirements: quantitative measurement; formation on the basis of priority basic indicators of regional development; accounting for the main components of development: institutional, environmental, economic and social.The proposed methodology is characterized by simplicity of calculation, low cost application, as well as the fact that the information base is made up of official data of state statistics bodies, which ensures their accessibility and comparability.